European business schools and global leadership: an examination of the admission criteria of the european master in management programs ranked by the Financial Times 2010 - Lehmann, Julian (2011)
The increase of internationally operating companies requires the development of global leaders to put strategies into practice. Although this development process is important to the corporate world, many future executives are graduates from top business schools which are closely linked to the business world and therefore play an important role in the process. This research examines whether the top European 'Master in Management' programs ranked by Financial Times in 2010 select those candidates that are best suited for global leadership development. Therefore, three previous meta-studies are synthesized to yield a profile of categorized competencies of a global leader. Then, information on admission criteria of the master programs is gathered and compared to this profile. Results show that six competencies are measured by more than half of the programs: English language proficiency, analytical ability (logical reasoning and quantitative), communication ability, global business knowledge, determination to achieve, motivation/drive and interpersonal ability. Furthermore, applicant skills are non-significant in the admission process and focus is on the analytical abilities. Comparison of the results to the previously developed comprehensive profile of a global leader indicates that a significant amount of programs might underestimate the meaning of personal abilities and traits for the development of global leaders.